PENERAPAN DIGITAL MARKETING SEBAGAI INFORMASI BARANG DAGANGAN DI PASAR NUSUKAN SOLO - Betty Gama; Yoto Widodo; Henny Sri Kusumawati; Yoppi Syahrial (LPPM Universitas Al Muslim, 2024)
ABSTRACT One form of application that can be used as a digital marketing medium is imooji. The imooji digital application was not yet known to market traders and was only discovered when the PKM team arrived. This community service activity aimed to increase participants' knowledge in understanding the concept of digital marketing using the imooji application, namely contents containing photos of merchandise found at market stalls. The participants in the activity were 8 traders and shop owners. The method of implementing activities was through the application of digital marketing, creating content for the imooji application. This is done because kiosk traders do not understand digital technology. Next, the team provided a brief explanation regarding the use of imooji which can be shared via social media such as WA, FB, and IG. The results of the implementation of the community service activities showed that not all participants are technologically literate and understand how to use imooji via cellphone because half of the participants are elderly, namely over 55 years, thus made it difficult to understand the imooji digital work process. Creating imooji content by providing a link containing a catalog of goods sold at market stalls can be easily shared with various participant social networks. This activity is expected to foster an entrepreneurial spirit in the digital era.